Since it's a cubic, we need to either use a trick or guess a solution. We can see that x=1 is a zero of the function ( 4*1 -3*1 - 1 = 0)
Since x = 1 is a zero, x-1 = 0, and
f(x) = (x-1) * (stuff)
To find what the "stuff" is, we need to do long division of polynomials.
stuff = (4x^3 - 3x - 1) / ( x - 1) I can't really show you how to do the long division here due to the type format, but I will try to explain it.
_____________
x-1 ) 4x^3 - 3x - 1 Now, x goes into 4x^3 4x^2 times, so our candidate answer is: 4x^2 + ....
-4x^3 +4x^2 Multiply 4x^2 * (x-1) and subtract from the line above.
4x^2 -3x x goes into 4x^2 4x times. Our revised candidate is: 4x^2 +4x + ...
-4x^2 +4x Multiply through again to get this line
x - 1 Subtract to get the x, then bring the -1 down from above
X-1 goes into x-1 exactly 1 time, so our solution is:
f(x) = (x-1) * (4x^2 + 4x + 1)
So f(x) = 0 if (x-1) = 0
(4x^2 + 4x + 1) = 0
The first part gives x=1 as a zero.
The second part factors as (2x+1)^2 = 0
This gives you a repeated root of x = -1/2
In summary, roots: x = 1, x = -1/2
Hope this helps :-)